Water and soil properties in organic and conventional paddies throughout the rice cultivation cycle in South Korea - Lee, Tae Gu; Lee, Chang Gu; Hong, Seung Gil; Kim, Jin Ho; Park, Seong Jik (Environmental Engineering Research, 2019)
Water and soil properties in paddy fields subjected to organic and conventional farming were characterized over the rice cycle in South Korea. To achieve the goals of this study, we sampled and analyzed soil and water from 24 organic paddy plots and 11 conventional paddy plots in March, May, August, and October 2016. The results were analyzed using statistical analyses, including analysis of variance (ANOVA), cluster analysis, and principal component analysis. The ANOVA results showed that water content (WC), electrical conductivity (EC), organic matter (OM), and available phosphorus (P2O5) in soil varied significantly (p < 0.01) depending on the farming method. Higher OM, EC, and P2O5 of soil were observed in the conventional paddies than in the organic paddies. All soil properties, except pH and ammonium, depended on seasonal variation. Cluster analysis revealed that soil properties in May were distinctly separated from those in other seasons mainly due to basal fertilization. The principal component analysis distinguished the soil properties in different seasons, but such a distinction was not observed between the soil properties in organic and conventional paddies. Low contents of WC, OM, and total N were observed in March. High concentrations of nitrate and total P were observed in May, but these were low in August and October. The soils from October were also characterized by high concentrations of EC and P2O5. These results indicate that the sampling time for soil and water can significantly influence the evaluation of soil properties with different farming methods.
Keywords: Available phosphorus; Conventional paddy; Electrical conductivity; Farming method; Organic paddy; Rice cultivation; Seasonal variation; Soil and water; Conventional paddy; Farming method; Organic paddy; Seasonal variation; Soil; Water